Magnetic Nanomaterials - Del Bianco, Lucia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The constant search for innovative magnetic materials increasingly leads to the creation of highly engineered systems built in different forms (films, wires, particles), structured on the nanoscale in at least one spatial direction, and often characterized by the coexistence of two or more phases that are magnetically and/or structurally different. In magnetic systems, the nanometric structural characteristics of the constituent elements, together with the type and strength of the magnetic interactions between them, determine the overall magnetic behavior and can lead to the appearance of unexpected and amazing magnetic phenomena. Indeed, the study of the magnetic properties of nanomaterials continues to arouse great interest for their intriguing fundamental properties and prospective technological applications. This Special Issue contributes to broadening the knowledge on magnetic nanomaterials, demonstrating the breadth and richness of this research field as well as the growing need to address it through an interdisciplinary approach. The papers collected in this book (two reviews and eight regular articles) report cutting-edge studies on the production and characterization of a variety of novel magnetic nanomaterials (nanoparticles, nanocomposites, thin films and multilayers), which have the potential to play a key role in different technologically advanced sectors, such as biotechnology, nanomedicine, energy, spintronics, data storage, and sensors.